Penyuluhan Strategi Lobi melalui Komunikasi Efektif dalam Meningkatkan Kesadaran Pengelolaan Sampah pada Siswa–Siswi di SDN Pejuang V Bekasi - Amelia Mahadewi Putri Kusmanto; Dina Kristina; Anasthasia Rachel Winarto; Eva Indah Lestari Simaremare; Salwa Nadiyah (CV. ITTC INDONESIA, 2026)
Sustainable waste management in elementary school environments remains a significant challenge, driven not only by a lack of supporting infrastructure but also by the limited capacity of students to act as agents of change in advocating for eco–friendly habits. Traditionally, educational approaches in schools tend to be instructive and top–down, positioning students as passive subjects of rules without equipping them with the courage and persuasive skills necessary to influence their peers or school authorities. In response to this phenomenon, this community service program aims to enhance waste management awareness among students at SDN Pejuang V Bekasi through an innovative approach: training in lobbying strategies integrated with effective communication. The employed method utilized a structured participatory training design consisting of three main stages: (1) building critical awareness of waste issues, (2) strengthening persuasive communication skills and basic negotiation techniques, and (3) practical application through lobbying role–play and mini–campaign mentoring within the school. The program's impact was evaluated using a one–group pretest–posttest design combined with participatory observation. The analysis results indicated a significant improvement across all measured indicators. Cognitively, there was a notable increase in the average scores of students' understanding of waste sorting. More crucially, from affective and psychomotor perspectives, students demonstrated a substantial boost in conf idence when articulating arguments, employing persuasive approaches with peers, and formulating negotiations with school authorities regarding the provision of supporting facilities. These findings confirm that building communication capacity and lobbying skills at an early age can transform students from passive rule–followers into active environmental advocates. This approach can serve as an effective alternative model for designing environment–based character education at the elementary school level.